Dendrite-free Sb-doped NASICON-type Na3Zr2Si2PO12 solid-electrolyte for stable solid-state sodium batteries - Akbar, Muhammad; Kim, Mingony; Moeez, Iqra; Bhatti, Ali Hussain Umar; Kim, Young Hwan; Jeong, Jiwon; Kim, Ji-Young; Park, Jae-Ho; Yu, Seungho; Chung, Kyung Yoon (Elsevier BV, 2025)
Solid-state sodium batteries (SSSBs) are gaining attention because of their safe operation, high energy density, and abundant raw materials. However, the high resistance, low ionic conductivity, and limited tolerance of solid electrolytes (SEs) to Na dendrites are the biggest obstacles for their commercialization. In this study, we synthesize a Sb-doped Na3Zr2Si2PO12 (NZSP) for the first time. The optimal Na3.1Zr1.9Sb0.1Si2PO12 (NZSbSP) sintered at 1200 degrees C exhibits improved Na-ion conductivity, high relative density, and excellent electrochemical stability. Moreover, the symmetry cell operation demonstrates exceptional compatibility with Na metal, and the Na0.9Zn0.22Fe0.3Mn0.48O2/NZSbSP/Na SSSB exhibits superior electrochemical performance, with a retention of 93.70 % after 50 cycles at 0.1C and 25 degrees C. Additionally, a postmortem study of the spent Na metal and SEs is performed using scanning electron microscopy and X-ray photoelectron spectroscopy at three different stages: (i) pristine, (ii) after contact with Na metal, and (iii) after 30 cycles. The improved relative density of NZSbSP suppresses the growth of Na dendrites during plating and stripping. These confirm the effectiveness of the Sb doping of NZSP in improving the ionic conductivity of NASICON SEs and suppressing Na dendrite formation for practical SSSBs.